2020
DOI: 10.3390/app10020434
|View full text |Cite
|
Sign up to set email alerts
|

Developing a New Computational Intelligence Approach for Approximating the Blast-Induced Ground Vibration

Abstract: Ground vibration induced by blasting operations is an important undesirable effect in surface mines and has significant environmental impacts on surrounding areas. Therefore, the precise prediction of blast-induced ground vibration is a challenging task for engineers and for managers. This study explores and evaluates the use of two stochastic metaheuristic algorithms, namely biogeography-based optimization (BBO) and particle swarm optimization (PSO), as well as one deterministic optimization algorithm, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The rest of the world uses approaches formulated by USBM and others [12][13][14][15]. Another more modern approach involving ECM (Error Correction Model) focuses on the application of forecast models [16][17][18]. These models are based on artificial neural networks (ANNs) and appear to be more precise, easily adjustable, and more predictable, and they avoid strictly formalized mathematical relations.…”
Section: Introductionmentioning
confidence: 99%
“…The rest of the world uses approaches formulated by USBM and others [12][13][14][15]. Another more modern approach involving ECM (Error Correction Model) focuses on the application of forecast models [16][17][18]. These models are based on artificial neural networks (ANNs) and appear to be more precise, easily adjustable, and more predictable, and they avoid strictly formalized mathematical relations.…”
Section: Introductionmentioning
confidence: 99%
“…Monjezi et al [21] used an artificial neural network (ANN) model which includes an input layer, two hidden layers, and an output layer to evaluate the ground vibration based on the Siahbisheh project, which demonstrates the effectiveness of using an ANN to predict the blast-induced ground vibration. Li et al [22] proposed two hybrid models using biogeography-based optimization (BBO), deterministic optimization algorithm (DIRECT), and artificial neural network, namely, BBO-ANN and DIRECT-ANN, and the generalization capability was found to be better than other prediction models. is study shows the use of an optimization algorithm to improve the prediction performance of the prediction model.…”
Section: Introductionmentioning
confidence: 99%
“…It then uses the smallest norm least square to arrive at the global solution. Within the recent years, the ELM approach has been extensively applied in several fields of sciences and engineering [27][28][29] including a few notable studies in blast-induced ground vibration prediction [30,31]. Prediction results from these studies have shown how well the ELM approach is able to generalise across the entire testing data.…”
Section: Introductionmentioning
confidence: 99%